Egg viability decreases rapidly with time since ovulation in the rainbow darter Etheostoma caeruleum: implications for the costs of choosiness. Issue 2 (11th December 2017) - Moran, R. L.; Soukup, R. M.; Zhou, M.; Fuller, R. C.
Abstract : Egg viability in the rainbow darter Etheostoma caeruleum, a fish apparently lacking female mate choice, was found to decline rapidly after ovulation. It was observed that the majority of a female's clutch may fail to hatch if she is prevented from mating for as little as 6 h. These data suggest that exercising female mate preferences may be selectively disfavoured in E. caeruleum due to the high cost of delaying mating.